Trajectories of Suicidal Ideation among Adolescents following Psychiatric Hospitalization - Wolff, Jennifer C. (J Abnorm Child Psychol, 2018)
Suicidal ideation (SI) is a common presenting problem for psychiatric hospitalizations in adolescents and often persists following discharge. This study examines whether distinct trajectories of SI could be delineated following hospitalization and the risk factors most strongly related to these trajectories. Adolescents (N = 104; 76 females; 28 males) were followed for 6 months after discharge from inpatient or partial hospitalization. Semi-parametric group modeling identified SI trajectory group membership. In all, 33.7% of adolescents fell in a Subclinical SI group, 43.3% in a Declining SI group, and 23.1% in a Chronic SI group. Multinomial logistic regression was utilized to examine baseline predictors of group membership. Emotion dysregulation differentiated Chronic SI from Declining SI. In multivariate analyses, adolescents endorsing greater non-acceptance of emotional responses (OR = 1.18) and more limited access to emotion regulation strategies (OR = 1.12) were more likely to belong to the Chronic SI than Declining SI trajectory. Those in the Chronic SI group also had the greatest number of suicide attempts and hospitalizations in the 6 months post-discharge. These results suggest that clinicians should closely monitor and address emotion dysregulation when assessing suicide risk. Greater dysregulation may require more intensive services in order to have an effect on chronic SI.